RNA sequencing data from: Aberrant expression of SLAMF6 constitutes a targetable immune escape mechanism in acute myeloid leukemia - Sandén, Carl; Lilljebjörn, Henrik; Fioretos, Thoas (Lund University, 2025)
This dataset includes RNA sequencing (RNA-seq) data from the HNT-34 AML (acute myeloid leukemia) cell line after knockout of the SLAMF6 gene by CRISPR/Cas9 (SLAMF6-KO) or mock-knockout with a construct targeting the firefly luciferase gene (SLAMF6-WT). Libraries were produced using the Illumina stranded mRNA prep kit and sequenced on an Illumina Novaseq 6000 system (Illumina). The dataset is available as merged transcripts per million (TPM) data for all cases generated using Salmon (salmon.merged.gene_tpm.tsv.gz). Raw sequencing reads (fastq) are available at the European Nucleotide Archive (ENA) under accession ID PRJEB90909: https://www.ebi.ac.uk/ena/browser/view/PRJEB90909. Published in: Sandén et al, Nature Cancer, 2025: https://www.nature.com/articles/s43018-025-01054-6
Keywords: Cancer cell biology; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi